Weather forecasting as an early warning system: pattern of weather forecast usage among coastal communities in Malaysia - Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Kamaruddin, Nurani; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Marsland Press, 2013)
The main objective of this study is to explore the patterns of weather forecasting usage among coastal communities in Malaysia. Focus group discussions (FGD) were held with two groups of communities at Kuala Paka Village in Dungun, Terengganu. A total of seven fishermen were involved in the first FGD, while a total of four housewives were involved in the second. The results show that the fishermen chose television as their main source of weather forecasting, while the housewives chose radio. For the respondents, particularly the fishermen, weather forecasting acts as an early warning system, and they accentuated the importance of weather self-monitoring before making their decision on whether or not to proceed with their fishing activities. In addition, the respondents reflected on the importance of information with regard to wind and waves, and stated that such information is vital for them, particularly during the northeast monsoon season.